Visual Processing Disorder in Children - Salai Dhavamathi Janarthanan (The Ophthalmology, 2017)
The minute persons think of eyesight, they generally think about accuracy, as in normal, 6/6 (or 20/20) vision. However, it is much more than that as the brain really processes the visual world, including things like symbols, pictures and distances. Faults in these brain tasks are called visual processing disorders (VPD) or visual processing issues. Many parents and teachers find it difficult to recognize the signs and symptoms of a VPD in their child or students. They also often confuse them with learning disabilities. This mini review aims to provide descriptions of visual processing issues and how to overcome through some vision, behavioral and education therapies.